2023
DOI: 10.2147/idr.s429990
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Fastidious Uropathogens Were Detected by M-PCR with Similar Prevalence and Cell Density in Catheter and Midstream Voided Urine Indicating the Importance of These Microbes in Causing UTIs

Dakun Wang,
Emery Haley,
Natalie Luke
et al.

Abstract: Introduction This study compared microbial compositions of midstream and catheter urine specimens from patients with suspected complicated urinary tract infections to determine if emerging and fastidious uropathogens are infecting the bladder or are contaminants. Methods Urine was collected by in-and-out catheter (n = 1000) or midstream voiding (n = 1000) from 2000 adult patients (≥60 years of age) at 17 DispatchHealth sites across 11 states. The two groups were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…42 Other studies identified VGS and CoNS in both midstream voided and catheter-collected specimens at similar prevalence and densities, further indicating the organisms' likely pathogenic nature. 43 Therefore, the approach of detecting only classical uropathogens may result in missed cases, as emerging or less common pathogens can cause infections and pose significant health threats.…”
Section: Discussionmentioning
confidence: 99%
“…42 Other studies identified VGS and CoNS in both midstream voided and catheter-collected specimens at similar prevalence and densities, further indicating the organisms' likely pathogenic nature. 43 Therefore, the approach of detecting only classical uropathogens may result in missed cases, as emerging or less common pathogens can cause infections and pose significant health threats.…”
Section: Discussionmentioning
confidence: 99%